2018
DOI: 10.1016/j.yebeh.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive benefits of the ketogenic diet in patients with epilepsy: A systematic overview

Abstract: The ketogenic diet (KD) has been found to be effective in reducing seizures in patients with treatment-refractory epilepsy. Less attention has been paid to additional cognitive benefits of KD. The aim of the present paper was to provide a comprehensive overview of the studies reporting effects on cognition after KD treatment in adults and children with epilepsy. To address this aim, the clinical literature on cognitive effects of KD in patients with epilepsy was reviewed using a systematic approach. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 77 publications
4
38
1
6
Order By: Relevance
“…For example, 31% of participants in this study reported cognitive benefits of MKD, including increased mental alertness and improved mood. It has previously been shown that MKD increases mental alertness, and that this is associated with both a reduction in seizures and diet itself [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, 31% of participants in this study reported cognitive benefits of MKD, including increased mental alertness and improved mood. It has previously been shown that MKD increases mental alertness, and that this is associated with both a reduction in seizures and diet itself [38].…”
Section: Discussionmentioning
confidence: 99%
“…25 Although it is difficult to establish firm conclusions due to confounding factors, the positive impact of DTs on cognition is widely acknowledged. [25][26][27] In patients with LGS with mitochondrial dysfunction, cognitive decline and seizures are important factors for treatment. In general, the cognitive status of LGS with mitochondrial dysfunction is too low to be evaluated, and cognitive status is difficult to quantify as a prognostic method due to the rarity of this pediatric condition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, strategies directed towards targeting the astrocytic glutamate transporter EAAT2 proved to be beneficial in alleviating the hyperexcitability symptoms associated with some neurodegenerative diseases and decrease the level of neurodegeneration in animal models of epilepsy (Kong et al, 2012(Kong et al, , 2014Goodrich et al, 2013;Zaitsev et al, 2019), ALS (Kong et al, 2014), PD (Chotibut et al, 2014;Hsu et al, 2015) and HD (Sari et al, 2010). Moreover, modulation of astrocytic energy metabolism via inhibition of lactate dehydrogenase (Sada et al, 2015;Rosati et al, 2018) or via ketonic diet (Valdebenito et al, 2016) had a neuroprotective effect in both animal models of PD (Shaafi et al, 2016), and patients with HD (Adanyeguh et al, 2015) and epilepsy (van Berkel et al, 2018). Also, treatments that targeted the suppression of the inflammatory NF-ÎșB pathway by increasing the expression of neurotrophic growth factor IGF-1 (Hu et al, 2018), or decreasing microglial proliferation (MartĂ­nez-Muriana et al, 2016), postponed the onset and slowed down the progression of motoneuron death in a mouse model of ALS.…”
Section: Glia As a Therapeutic Target For Treating Neurodegenerationmentioning
confidence: 99%